1975
DOI: 10.1520/jfs10290j
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Explosive Residues

Abstract: Examination of bomb scene evidence is an area of increasing involvement for the forensic scientist in which incidents may vary from student mischief to mass murder. To undertake explosive casework responsibilities, the scientist must have personal experience of the type of physical evidence left after explosions, including device remains, characteristic damage, and chemical residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The application of x-ray photoelectron spectroscopy (ESCA) to qualitative and quantitative analyses of surfaces has recently been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These results show that surface detection of trace elements in the sub-monolayer region (SO4 g/cm2) is possible ( 2 , 5 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of x-ray photoelectron spectroscopy (ESCA) to qualitative and quantitative analyses of surfaces has recently been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). These results show that surface detection of trace elements in the sub-monolayer region (SO4 g/cm2) is possible ( 2 , 5 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, one of the most widely used methods for the analysis of explosives is thin-layer chromatography (TLC) (10,11). Identification has relied primarily on comparison with standard (Rf) values, followed usually by spot tests and/or infrared spectroscopy to confirm the presence of nitrates, nitrites, or other common functionalities.…”
mentioning
confidence: 99%
“…Traditionally, chemical spot tests4 and X‐ray powder diffraction5 are the methods used by most forensic laboratories for the analysis of inorganic explosives. As the amount of sample required is usually high, these methods sometimes limit the detection of some inorganic ingredients in the explosive samples.…”
mentioning
confidence: 99%
“…The certainty with which the analysis of the IR spectrum can provide definitive identification of a material greatly increases if a prior chemical separation is employed. a Adapted from the articles by Yinon (2) and by Pristera et al (26) Beveridge et al (37) reported that, in a large number of analyses of explosive residues, IR spectroscopy detected explosive components in 50% of the tests in contrast to 80% for thin-layer chromatography. Thus, IR spectroscopy is a good confirmatory test if sufficient quantity of sample is available.…”
Section: Tunable Infrared Laser Differential Absorption Spectroscopy mentioning
confidence: 99%